Expressions of miR-199a-5p and miR-125b-5p and their target genes in the endometrium of recurrent implantation failure patients following in uterus infusion of autologous peripheral blood mononuclear cells - Azarpoor, Azita; Ardeshirylajimi, Abdolreza; Mohammadi Yeganeh, Samira; Pourmatrood, Elham; Dehghan, Zeinab; Farifteh Nobijari, Fattaneh; Salehi, Mohammad (Trends in Immunotherapy, 2022)
Despite numerous advances in fertility techniques, some individuals experience implantation failure. One of the therapeutic approaches is the study of immunological aspects of the implantation process in recurrent implantation failure (RIF) patients. Peripheral blood mononuclear cell (PBMC) therapy and platelet-rich plasma are currently available cell therapies. The aim of this study was to determine the expressions of the FGFR-2 and LIF genes that are regulated by miR-199a-5p and miR-125b-5p. These genes play a fundamental role in implantation in RIF patients treated with PBMCs. 20 patients clinically diagnosed with RIF were randomly assigned to a RIF patient with PBMCs intrauterine infusion group (n = 10) and RIF group (n = 10). Normal, healthy females (n = 10) comprised the control group. In order to examine the efficacy of the PBMCs injection in the treatment group, expressions of miR-199a-5p and miR-125-5p and FGFR-2 and LIF as their target genes, were evaluated in all three groups and were compared the results. We discovered that the RIF group had higher expressions of miR-199a-5p and miR-125-5p along with decreased expressions of their target genes. However, both FGFR-2 and LIF gene had elevated expressions in the RIF patients with PBMCs intrauterine infusion group compared to the RIF group, with significant decrease in miR-199a-5p and miR-125b-5p reciprocally. The treatment with PBMCs can be effective in changing the expression of microRNAs and genes associated with endometrial receptivity and by changes in the expression of them and their role during embryo development improve this process.